2009
DOI: 10.1093/nar/gkp793
|View full text |Cite
|
Sign up to set email alerts
|

The HSV-1 ICP27 RGG box specifically binds flexible, GC-rich sequences but not G-quartet structures

Abstract: Herpes simplex virus 1 (HSV-1) protein ICP27, an important regulator for viral gene expression, directly recognizes and exports viral RNA through an N-terminal RGG box RNA binding motif, which is necessary and sufficient for RNA binding. An ICP27 N-terminal peptide, including the RGG box RNA binding motif, was expressed and its binding specificity was analyzed using EMSA and SELEX. DNA oligonucleotides corresponding to HSV-1 glycoprotein C (gC) mRNA, identified in a yeast three-hybrid analysis, were screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…Recently, we reported that several GC-rich sequences from the glycoprotein C (gC) gene, which were derived as 30-mers from a 300-nucleotide clone that was positive for ICP27 binding in a yeast three-hybrid screen (5), bound the N-terminal portion of ICP27 from amino acids 1 to 160 in EMSAs (5,6). This portion of ICP27 includes the RGG box from residues 138 to 152 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we reported that several GC-rich sequences from the glycoprotein C (gC) gene, which were derived as 30-mers from a 300-nucleotide clone that was positive for ICP27 binding in a yeast three-hybrid screen (5), bound the N-terminal portion of ICP27 from amino acids 1 to 160 in EMSAs (5,6). This portion of ICP27 includes the RGG box from residues 138 to 152 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ICP27 was shown previously to bind RNA through an RGG box motif located at amino acids 138 to 152 within the 512-amino-acid protein (28,34). Using electrophoretic mobility shift assays (EMSAs), we showed that the N-terminal portion of ICP27 from amino acids 1 to 160 bound specifically to viral oligonucleotides that are GC rich and that are flexible and relatively unstructured (5). Here we report the importance of three arginine residues within the RGG box for ICP27 binding to GC-rich sequences in vitro and for viral RNA export during infection.…”
mentioning
confidence: 88%
See 3 more Smart Citations